Perspectives on library services: Utilization and satisfaction of undergraduate students - Lasig, Camia; Madia, Roselyn M.; Reyes, Nuelah SJ.; Morales, Vanessa B.; Garabiles, Richie N. (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2025)
Background of the study: For libraries to be relevant and efficient, their services must adapt to the changing requirements and preferences of its patrons. Continuous development requires an understanding of how undergraduate students use the resources and services provided by libraries, as well as how satisfied they are with these offerings. Purpose: The purpose of this study is to determine undergraduate usage patterns, satisfaction levels, and perspectives about the staff, resources, services, and facilities provided by the university library. Method: This study employs a descriptive survey design to explore the utilization and satisfaction of library services and facilities among undergraduate students and the collected data were analyzed using both quantitative and qualitative methods. Findings: The study reveals that undergraduate students at Central Luzon State University frequently utilize the university library, primarily for academic and research purposes. Overall, students express high levels of satisfaction with the library personnel, the collection of books and theses, security facilities, the process for returning materials, and orientation services. However, critical areas needing improvement include increasing staff numbers, updating the library collection, providing more chairs and tables, and enhancing internet connectivity. Conclusion: The library is a crucial component in molding the learning environment of any successful academic institution. Identifying and addressing areas that need improvement is crucial for both maintaining and improving student satisfaction, as well as efficiently fulfilling their academic requirements.